Comparison of post mastectomy cicatrization among women with or without diabetes mellitus - Marislei Sanches Panobianco; Bárbara Alexandre Lespinassi Sampaio; Edilaine Assunção Caetano; Aline Inocenti; Thais de Oliveira Gozzo (Rev Rene)
This a Cross-sectional quantitative study which aimed to compare the efficiency of the cicatrization process of post-surgical mastectomy, among women who have diabetes mellitus or not. It was accomplished between March and June 2009 in a nucleus of rehabilitation of mastectomized women in a town in the countryside of São Paulo. A form was filled out by 22 women (11 diabetic and 11 non-diabetic). It consisted of (personal, demographic issues, and others related to the surgery). The data were analyzed using descriptive statistics. We could observe that the occurrence of dehiscence of the operatory wound was the same (72,8%) for both groups, but the presence of exudates, odor and inflammation signs, was higher among diabetic women. The biggest cicatrization problems occurred among diabetic carriers. The results may help patients and health professionals improve strategies for diabetes management and healing after surgery.